Risk Management Strategies in Project Negotiations - Hossain, Mohammad Alauddin (My University, 2025)
This research investigates performance risks which emerge during vendor negotiations in Bangladesh’s fast-growing e-commerce market. The research examines the risk management techniques project managers implement for vendor-related challenges while dealing with the constraints of politics, economy, society, technology, environment and law. A PESTEL framework provides the analysis framework to assess external factors' impact on vendor project results and performance. The study identifies protective techniques that project managers implement to control delivery interruptions, monetary uncertainties, cybersecurity threats and regulatory compliance issues. The study provides specific implementation insights about vendor relationship management as well as risk management strategies through stakeholder interviews combined with contract analysis. In this research capacity to combine AI along with predictive analytics to improve negotiation methods while reducing performance related risks is explored. The findings add to the knowledge about how to negotiate with vendors in a way that the e-commerce sector of Bangladesh may successfully navigate complexities to achieve sustainable growth and achieve project success.
Keywords: risk management; negotiations; risks; commerce; project management; fi=Tuotantotalous (tekniikka)|en=Industrial Management and Engineering|; Master's Programme in Industrial Management; Strategic Project Management